Rotational flattening of planets - Pacheco, J. A. de Freitas (Cadernos de Astronomia, 2024)
Rotating celestial bodies do not have spherical symmetry, since the effective gravity isdifferent between the poles and the equator. Deviation from sphericity, dubbed the flatteningof the body, depends on the rotation velocity but also on the internal structure. In this articlethe flattening of solar system planets is calculated by considering these bodies either as anincompressible fluid or constituted by an elastic material. Comparison with data permits toobtain information about the internal structure of these bodies.
Keywords: flattening of planets; rotational flattening